The five queer books that helped me come out | Xtra Magazine - Schriefer, Natalie (Xtra, 2022)
These five recent memoirs are queer books that helped me come out, echoing my own life, sometimes in unexpected ways
Keywords: dept.hhs

Learning Self-Compassion - Distancesays, November 20th-Critical (Into The Spine, 2022)
With a little help from Zelda.
Keywords: dept.hhs

Opinion | The reckless way I avoided student debt - Schriefer, Natalie (NBC News, 2022)
I worked three jobs to avoid student debt. Many students find themselves in a similar vulnerable spot, choosing to either face burnout now or later.
Keywords: dept.hhs

So They Didn’t Say Yes: How A Scholarship Rejection Taught Me to Work Smarter - Schriefer, Natalie (Author, 2022)
Three years ago, I graduated from my MFA program. I wanted to hit the ground running, so right from the start, I crafted myself a ritual: around the first of each month, I’d spend a morning scouring listservs and social media for writing opportunities. I tracked submissions calls, literary magazine
Keywords: dept.hhs

For Kids in the Hospital, Video Games Are Part of Recovery - Schriefer, Natalie (Wired, 2022)
In-house gaming technology specialists play with and support the youngest patients. Plus, research shows that playtime gives literal health points.
Keywords: charity; dept.hhs; gaming culture; health care; video games

Here's Why The 'Don't Say Gay' Bill Won't Work - Schriefer, Natalie (Ms. Magazine, 2022)
The flaw in Florida’s “Don’t Say Gay” bill and Texas's anti-trans child abuse directive: They will hurt LGBTQ kids, students and teens.
Keywords: dept.hhs

How to Cope With Post-Game Depression - Schriefer, Natalie (Wired, 2022)
Congratulations, you beat your favorite video game. Now it’s time to beat the feelings of emptiness.
Keywords: dept.hhs; gaming culture; mental health; psychology; video games

Cold Reality: Revisions of War in John Knowles’ “Phineas” and A Separate Peace – Irish Journal of American Studies - Schriefer, Natalie (Irish Journal of American Studies, 2022)
Keywords: dept.hhs; peer-reviewed; ⛔ No DOI found

Coalition Building and Food Insecurity: How an Equity and Justice Framework Guided a Viable Food Assistance Network - Santilli, A.; Lin-Schweitzer, A.; Morales, S.I.; Werlin, S.; Hart, K.; Cramer, J.; Martinez, J.A.; O’Connor Duffany, K. (International Journal of Environmental Research and Public Health, 2022)
Food insecurity is widespread in the United States. The COVID-19 pandemic intensified the need for food assistance and created opportunities for collaboration among historically-siloed organizations. Research has demonstrated the importance of coalition building and community organizing in Policy, Systems, and Environmental (PSE) change and its potential to address equitable access to food, ultimately improving population health outcomes. In New Haven, community partners formed a coalition to address systems-level issues in the local food assistance system through the Greater New Haven Coordinated Food Assistance Network (CFAN). Organizing the development of CFAN within the framework of Collaborating for Equity and Justice (CEJ) reveals a new way of collaborating with communities for social change with an explicit focus on equity and justice. A document review exploring the initiation and growth of the network found that 165 individuals, representing 63 organizations, participated in CFAN since its inception and collaborated on 50 actions that promote food access and overall health. Eighty-one percent of these actions advanced equitable resource distribution across the food system, with forty-five percent focused on coordinating food programs to meet the needs of underserved communities. With the goal of improving access to food while addressing overall equity within the system, the authors describe CFAN as a potential community organizing model in food assistance systems. © 2022 by the authors.
Keywords: chronic disease prevention; coalition building; dept.hhs; environment change; food insecurity; peer-reviewed; policy; systems